A new device to measure the changes in blood volume during pulseatile cycle non-invasively - Mohamed, A.H.; Moghavvemi, M.; Ibrahim, W.M.A.W. (2008)
An improved technique, for the non-invasive measurement of blood component abnormalities based on the electrical admittance cuff is designed. Together with blood pressure (BP) and arterial elasticity represented as volume elastic modulus, in human upper arm. A simple data acquisition system is used to sense the changes in pressure by using the normal cuff that is used in sphygmometer (mmHg), and incorporated with bioelectrical impedance apparatus using three frequencies (100 KHz, 1 MHz and 3.2 MHz). This technique depends on the continuous measuring of the blood impedance simultaneously with the blood pressure in the cuff. These measurements technique showed that the blood electrical components can be measured.